To what extent have laterites contributed to the geochemical, surface reflectance and magnetic properties of adjacent tropical soils? Evidence from Niger and Burkina Faso. Issue 15 (22nd September 2017) - Hunt, A.; Oldfield, F.; Bloemendal, J.; Boyle, J. F.; Chiverrell, R. C.; Lyons, R.; Shen, Z.; Williams, E. R.; Balsam, W.
Abstract: The present study is based on a suite of surface samples from exposures of eroded laterite, considered to be Tertiary in age, and nearby soils in the Sahelian region of SW Niger and Burkina Faso. X‐ray fluorescence, X‐ray diffraction, computer‐controlled scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, diffuse UV–visible reflectance spectroscopy and a suite of magnetic measurements have been used to shed light on the origin of the soils and their possible derivation from the adjacent, eroded laterite outcrops. On the basis of the wide range of data obtained, we conclude that the mineralogy and magnetic properties of the soils preclude direct derivation from the laterites without further weathering and modification. Nor does the evidence support the view that the soils have evolved entirely independently, uninfluenced by input from the laterites. The only conclusion that is consistent with all the lines of evidence is that the erosion of the laterites provided at least a significant part of the material upon which soil formation took place. This must have occurred at a time early enough to permit a long period of subsequent soil development during which the iron oxides, specifically haematite and ferrimagnetic minerals, were significantly modified. From this, we infer that eroded material from discontinuous laterite exposures has contributed significantly to the remotely sensed, distinctive reflectance characteristics of the Sahel surfaces. The magnetic properties of the soils provide evidence for the in situ neo‐formation of fine, secondary, pedogenic magnetite/maghemite grains typical of those found in many soils across the Sahel region and elsewhere in both temperate and tropical environments. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We studied eroded laterites and adjacent soils in the Sahel. Magnetic, geochemical, mineralogical, colour, and individual particle analyses were used to determine the origin of the soils. We conclude (i) the mineralogy and magnetic properties of the soils preclude direct derivation from the laterites; (ii) there is no evidence that the soils evolved independently without laterite input; (iii) laterite erosion provided a significant part of the material for soil formation; and (iv) eroded laterite has contributed significantly to the remotely sensed reflectance characteristics of the Sahel surfaces.